Mr Juan Lucas Restrepo Ibiza, Chairperson Global Forum on Agricultural Research (GFAR) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Inaugural meeting of the Global Alliance for Climate-Smart Agriculture. New York, 24 September 2014. Find out more: http://www.climatesmartagriculture.org